Shapeable large-pore electrospun polycaprolactam cotton facilitates the rapid formation of a functional tissue engineered vascular graft. (June 2020) - Chen, Dian; Zhang, Lei; Zhang, Wen; Tang, Ziqing; Fu, Wei; Hu, Renjie; Feng, Bei; Hong, Haifa; Zhang, Haibo
Abstract: Tissue engineered vascular grafts (TEVGs) with diameters <6 mm have broad applications. However, maintaining graft post-implantation patency and function is still difficult to achieve and of urgent necessity. In this study, we use an effective strategy to make the large-pore electrospun polycaprolactone (PCL) cotton material (Cotton) and utilized immunoreactive pre-cultivation to prepare a small diameter autologous TEVG. The material assessment via scanning electron microscopy revealed that Cotton has favorable characteristics that make it suitable for immunoreactive pre-cultivation. It also possesses great mechanical properties. Due to strong reshape ability of Cotton, designed vascular patch and vascular scaffold and others could be obtained. For vascular scaffold, Cotton was wrapped around a polytetrafluoroethylene (PTFE) tube and implanted subcutaneously in rats for up to 2 weeks to prepare autologous TEVGs. Autologous TEVGs were then transplanted into the abdominal aorta of the same rat. Cotton TEVG formed functional graft with favorable patency after transplantation for 4 weeks. Histological results showed that the TEVGs had characteristics similar to that of the native aorta. Our results indicate PCL cotton material could be a kind of shapeable material and used to create a promising biocompatible and functional vascular graft over a relatively short period of time. Graphical abstract: Unlabelled Image Highlights: Large-pore polycaprolactone cotton material was fabricated by electrospinning technique in an innovative condition. The cotton material is highly shapeable and customizable in combination with 3D printing technique. The cotton material facilitates cell infiltration forming autologous tissue with high mechanical strength. The cotton material provides a method for rapid autologous vascular graft engineering.